Server Worker Power Optimization with Virtual Machine Live Migration Technique Using Fuzzy Mamdani - Azzahari, Muhammad; Khaldun, Ibnu; Mahmud, Mahmud; Rozaliana, Rozaliana (Politeknik Negeri Lhokseumawe, 2025)
This study focuses on power optimization of worker servers by applying live migration techniques for virtual machines (VMs) using the Mamdani fuzzy logic method. The main goal is to automatically move VMs to servers with lower CPU usage, thereby reducing overall power consumption. The system was built using the Proxmox VE platform and simulated for 30 minutes under two conditions: without and with Mamdani fuzzy logic. The results show that the use of fuzzy Mamdani reduces power consumption by 0.26 watts compared to the non-migration system. Although the savings may seem minor, the method is effective when applied at a larger data center scale. This technique enables efficient workload distribution by migrating VMs, allowing idle servers to reduce energy usage. In conclusion, Mamdani fuzzy logic offers a practical solution for energy-saving in cloud computing environments without compromising system performance.